Development Of Small Plastic in the Territory of Central Asia - Tairova Kholida Khamidovna (Peerian Journals Publishing, 2022)
This article discusses the role of fine art in sculpture and its role in compositional and plastic modeling of images in volumetric form and a particular material.
Keywords: Sculpture; art; small plastic; relief